Pemberian terapi kombinasi range of motion (ROM) dengan rangsang taktil dalam meningkatkan kekuatan otot pada pasien CVA - Syamsiyah, Alfiatus; Husna, Chairul Huda Al (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stroke is a neurological disorder that can cause muscle weakness, decreased sensory function, and impaired physical mobility. Range of Motion (ROM) therapy and tactile stimulation are forms of non-pharmacological therapy that can help improve motor and sensory function in post-stroke patients. Purpose: To determine the effect of ROM therapy and tactile stimulation on improving motor and sensory abilities in post-stroke patients, focusing on changes in joint range of motion (ROM) and increased tactile sensation response after one week of intervention. Method: This case study was conducted on one patient diagnosed with impaired physical mobility due to a Cerebrovascular Accident (CVA). The intervention, consisting of ROM therapy and tactile stimulation, was administered for one week, with progress measured using a joint range of motion (ROM) assessment sheet and tactile sensation scoring. Results: The patient's initial ROM score was 24 and tactile sensation was 5, indicating limited movement and decreased sensation. After one week of intervention, the ROM score increased to 28 and tactile sensation to 7, indicating improved muscle strength and tactile recognition. Conclusion: The application of ROM therapy and tactile stimulation has been proven effective in increasing muscle strength and sensory function in stroke patients, thus helping to improve physical mobility and support the restoration of independence in functional activities. Keywords: Cerebrovascular Accident; Range of Motion (ROM) Therapy; Tactile stimulation. Pendahuluan: Stroke merupakan gangguan neurologis yang dapat menyebabkan kelemahan otot, penurunan fungsi sensorik, serta gangguan mobilitas fisik. Terapi Range of Motion (ROM) dan rangsang taktil merupakan bentuk terapi non-farmakologis yang dapat membantu meningkatkan fungsi motorik dan sensorik pada pasien pasca stroke. Tujuan: Untuk mengetahui pengaruh terapi ROM dan rangsang taktil terhadap peningkatan kemampuan motorik dan sensorik pada pasien pasca stroke dengan memfokuskan pada perubahan rentang gerak sendi (ROM) serta peningkatan respon sensasi sentuhan setelah dilakukan intervensi selama satu minggu. Metode: Studi kasus ini dilakukan pada satu pasien dengan diagnosa gangguan mobilitas fisik akibat Cerebrovascular Accident (CVA). Intervensi berupa terapi ROM dan rangsang taktil diberikan selama 1 minggu, dengan pengukuran perkembangan menggunakan lembar penilaian rentang gerak sendi (ROM) dan skoring sensasi taktil. Hasil: Skor ROM pada awal pengukuran pasien sebesar 24 dan sensasi taktil 5, hal ini menunjukkan keterbatasan gerak dan penurunan sensasi. Setelah dilakukan intervensi selama satu minggu, skor ROM meningkat menjadi 28 dan sensasi taktil menjadi 7 yang menunjukkan adanya peningkatan kekuatan otot dan kemampuan mengenali sentuhan. Simpulan: Penerapan terapi ROM dan rangsang taktil terbukti efektif dalam meningkatkan kekuatan otot dan fungsi sensorik pada pasien stroke, sehingga dapat membantu memperbaiki mobilitas fisik dan mendukung pemulihan kemandirian aktivitas fungsional. Kata Kunci: Cerebrovascular Accident; Rangsang taktil; Terapi Range of Motion (ROM).